2017
DOI: 10.14348/molcells.2017.0011
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Controlling Microglia Chemotaxis

Abstract: Microglia are the primary resident immune cells of the central nervous system (CNS). They are the first line of defense of the brain’s innate immune response against infection, injury, and diseases. Microglia respond to extracellular signals and engulf unwanted neuronal debris by phagocytosis, thereby maintaining normal cellular homeostasis in the CNS. Pathological stimuli such as neuronal injury induce transformation and activation of resting microglia with ramified morphology into a motile amoeboid form and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 48 publications
4
50
0
Order By: Relevance
“…The DA-induced increase in cell spreading was also recapitulated in resting BV 2 microglia cells ( Figure 1B ). Recent evidences indicated that microglia exhibit two functionally different activation states that are referred to as classical (pro-inflammatory, M1) and alternative activation (anti-inflammatory, M2) ( Yang et al, 2017 ). Microglia exposed to LPS, a common stimulus that triggers a pro-inflammatory phenotype (M1 activated microglia) exhibited increased expression of IL-6 and iNOS, amoeboid morphology, and increased phagocytic activity ( Figures 1C , 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…The DA-induced increase in cell spreading was also recapitulated in resting BV 2 microglia cells ( Figure 1B ). Recent evidences indicated that microglia exhibit two functionally different activation states that are referred to as classical (pro-inflammatory, M1) and alternative activation (anti-inflammatory, M2) ( Yang et al, 2017 ). Microglia exposed to LPS, a common stimulus that triggers a pro-inflammatory phenotype (M1 activated microglia) exhibited increased expression of IL-6 and iNOS, amoeboid morphology, and increased phagocytic activity ( Figures 1C , 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate that exogenous LPA induced activation of the PKD, MAPK, and AKT pathways, as well as phosphorylation of NF-κB, STAT1, STAT3, and c-Jun in a CRT0066101-sensitive manner both in BV-2 and PMM. All of these signaling pathways were reported to be involved in microglial polarization [ 77 ] and chemotaxis [ 78 ]. These findings indicate a sensor function for LPAR5 that transmits intracellular signals via PKD isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathways involved in microglia chemotaxis are highly complex. Briefly, studies have highlighted the specific roles of extracellular signal–regulated kinases (ERK1/2), protein kinase A (PKA), phospholipase A2 (PLA2), phosphoinositide 3-kinase (PI3K), and ATP/purinergic receptor signaling pathways in regulating microglial migration (Fan et al, 2017 ). Monocyte chemoattractant proteins (MCPs) are of particular interest in neuroinflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%